The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1017/s0144686x14000038
|View full text |Cite
|
Sign up to set email alerts
|

Ages and Stages: the place of theatre in the lives of older people

Abstract: Despite the growing interest amongst gerontologists and literary and cultural scholars alike, in arts participation, ageing and the artistic outputs of older people, comparatively little attention has yet been paid to theatre and drama. Likewise, community or participatory theatre has long been used to address issues affecting marginalised or excluded groups, but it is a presently under-utilised medium for exploring ageing or for conveying positive messages about growing older. This paper seeks to address this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…Drama therapy techniques fortify this social process and enrich it with unique advantages. The ability to be part of a creative group, in which each member has his/her own unique and essential role in a dramatic creation, strengthens the individual's sense of relevance and the involvement of the elders in their own community (Bernard et al, 2015). The process of playing a role in the dramatic picture of the personal stories of others requires an emotional, cognitive, and behavioral understanding of the other (Kellermann, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drama therapy techniques fortify this social process and enrich it with unique advantages. The ability to be part of a creative group, in which each member has his/her own unique and essential role in a dramatic creation, strengthens the individual's sense of relevance and the involvement of the elders in their own community (Bernard et al, 2015). The process of playing a role in the dramatic picture of the personal stories of others requires an emotional, cognitive, and behavioral understanding of the other (Kellermann, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…A search for prior studies in the area of drama therapy for the elderly yielded a very limited number of studies (Beard, 2012;Mechaeil, Graybow, & Cobham, 2010;Peleg, Lev-Wiesel, & Yaniv, 2014;Reinstein, 2002). The few studies that were found indicated that drama is a significant therapeutic tool in itself, allowing an elderly person to feel creative, spontaneous, and spiritual À feelings that constitute a significant resource when addressing the challenges posed by old age (Bernard et al, 2015;CastoraBinkley, Noelker, Prohaska, & Satariano, 2010;Noice, Noice, & Kramer, 2014.…”
Section: Drama Therapy and Life-reviewmentioning
confidence: 99%
“…In the area of health humanities, virtually all conceivable art genres are relevant. In this article, we focus on four genres, given the body of empirical knowledge: novels, films, paintings and music (opera, theatre and poems are excluded but see Bernard et al (2015) , and Seymour and Murray (2016)) .…”
mentioning
confidence: 99%
“…Overall, the findings of existing literature, including the New Dynamics of Ageing programme, broadly resonate with those of our own 'Ages and Stages' projects (Bernard et al, 2015), and have underpinned our curriculum development activities. These findings include:…”
Section: A Growing Evidence Base?mentioning
confidence: 61%